Integrasi Nilai-nilai Islam dalam Lingkungan dan Aktivitas Pembelajaran di SDN Batu Ampar 10 Pagi - Aprilianti, Dwi Arum; Utami, Elvira; Nuraeni, Heni Ani (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This research aims to investigate the implementation of Islamic values ​​in the learning environment and activities at SDN Batu Ampar 10 Pagi. The method used is qualitative research with a descriptive design. Data were collected through interviews, observations, and documentation involving a number of informants, including class teachers and vice principals. The results of the study indicate that the implementation of Islamic values ​​has been carried out through morning activities, such as joint prayer, congregational prayer, celebration of religious holidays, and charity activities on Fridays. In addition, in the learning process, Islamic values ​​are inserted into various lessons by linking teaching materials with religious principles, such as the significance of prayer, ethics, and discipline in the classroom. These activities are intended to shape the character of students who have noble ethics and actions, are responsible, and have spiritual awareness. The challenges faced include differences in student backgrounds and minimal support from families. Therefore, good cooperation between teachers and parents is very important. This is crucial to ensure the implementation of Islamic values ​​continues, both at school and at home. This study emphasizes the importance of the function of education in creating a generation that is intelligent, moral, academic and has character.